Case report Paraganglioma of the lumbar spinal canal – case report - Słowiński, Jerzy; Stomal, Monika; Bierzyńska-Macyszyn, Grażyna; Świder, Kazimierz (Folia Neuropathologica, 2005)
We present the case of a 46-year-old female with a lumbar spine paraganglioma. The patient complained of a right-sided lumboischialgia. Preoperative MRI revealed an intradural tumour at the vertebra L3 level, located in the midline, 7 mm in diameter. The tumour was totally removed by laminectomy. Histopathological examination showed nests of chief cells (zellballen), surrounded by reticulin fibres. Immunohistochemistry showed a positive reaction for chromogranin A, neuronal specific protein, synaptophysin and cytokeratin in the chief cells. The sustentacular cells displayed immunopositivity for S-100 protein, single cells were also positive for GFAP. We found no proliferative activity in the tumour cells (Ki-67 index = 0%). In the two years follow-up the patient remains without clinical or radiological signs of recurrence. Spinal paraganglioma is a rare, surgically curable tumour with low proliferative potential. This entity should be taken into consideration in the differential diagnosis of extramedullary spinal lesions.